An Assessment of the Knowledge, Attitude and Practices (KAP) of Dog Owners regarding Pet Reproduction - Singh, Bilawal; Singh Ghuman, Sarvpreet; Singh, Amandeep; Singh, Parminder (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
An ex-post facto study was designed to investigate the knowledge, attitude and practices (KAP) of the dog owners visiting the Multi Speciality Veterinary Hospital, Guru Angad Dev Veterinary and Animal Sciences University, Ludhiana (India). A total of 102 dog owners were investigated purposively to assess their socio-economic profiles, knowledge, attitude, and practices regarding pet reproduction with major focus on breeding management and artificial insemination. On analysis, results revealed that majority of the respondents were young (19-35 years), and belonged to low-income category (earning less than Rs. 3.00 lakh annually). A substantial portion of dog owners had low experience in pet rearing, with a majority owning large breed dogs. The study highlighted gaps in knowledge related to reproductive management, with only 40.20% of respondents aware of semen storage temperatures and 49.02% familiar with semen cryopreservation. However, 86.27% of the respondents knew the average litter size, and 84.31% were aware of the appropriate age for female dogs to begin breeding. Overall, 50.98% of respondents demonstrated a high level of knowledge, which was positively correlated with higher education levels. Majority of the respondents (57.84%) exhibited a favourable attitude toward pet reproduction practices, particularly neutering. However, only 48.04% maintained breeding records, and 64.71% provided adequate care for pregnant or whelping dogs. The findings emphasize the need for improved awareness and education on advanced reproductive technologies and ethical breeding practices.
Keywords: Artificial insemination; KAP; Pet breeding; Reproduction